Modification Of Learning Media To Improve Learning Keys Effectiveness On Lempar Lembing, Classroom Action Research In Class X Sman 2 Painan - Pisyahri Rajab (Fakultas Sastra Universitas Ekasakti, 2017)
This situation and condition has been going on for quite a while and the school until this moment has not been able to fulfill the means of the disc to sufficient limits or ideal conditions, for example by a ratio of 1: 2 (1 disc for 2 persons). This is understandable, because schools have a lot of needs and almost all have a high level of urgency to meet by the school. So demanding schools to provide discs in accordance with ideal conditions, is unrealistic and can further lead to unfavorable climate and climate in schools.